Changes of gait parameters and lower limb dynamics in recreational runners with achilles tendinopathy - Kim, SungJoong; Yu, JaeHo (Journal of sports science & medicine, 2015)
This study aimed to clarify the mechanical gait changes caused by achilles tendinopathy by comparing gait parameters and changes in hip, knee, and ankle moments between an experimental group (EG) and a control group (CG). Twenty runners with achilles tendinopathy were included in the EG (male/female: 10/10, age: 27.00 ± 4.63), and 20 CG (male/female: 10/10, age: 27.25 ± 4.33) participants were recruited. Subjects walked a 13-m distance at their normal walking speed 5 times to obtain motion analysis and joint moment data. Gait parameter analysis showed significant differences in double-limb support (EG: 22.65 ± 4.26%, CG: 20.37 ± 4.46%), step length (EG: 0.58 ± 0.0 7m, CG: 0.64 ± 0.08 m), step width (EG: 0.16 ± 0.04 m, CG: 0.14 ± 0.05 m), stride time (EG: 1.09 ± 0.10 second, CG: 1.05 ± 0.08 second), and walking speed (EG: 1.09±0.18 m·s(-1), CG: 1.23 ± 0.17 m·s(-1)) between the 2 groups (p < 0.05). Significant differences were found in hip joint moment for initial contact, mid-stance, terminal stance, and pre-swing phases; knee joint moment for initial contact and pre-swing phases; and ankle joint moment for pre-swing and terminal swing phases (p < 0.05). Gait parameters and hip, knee, and ankle moments were altered in runners with achilles tendinopathy. Thus, clinical features of gait changes should be understood for optimal treatment of achilles tendinopathy; further research is required in this field. Key pointsA reduction in gait parameters, namely, step length, stride length, and walking speed, and an increase in double-limb support occurs in runners with achilles tendinopathy.A reduction in the hip extension moment occurs during the initial contact, as well as a reduction in the knee flexion moment from the mid-stance to pre-swing phases, a continuous decrease in the knee flexion moment from the early stance phase, and a reduction in the extension moment during the terminal stance phase.A reduction in the ankle plantar flexion moment occurs from the mid-stance phase and that a reduction in the dorsiflexion moment occurs during the terminal swing phase.